Vasodilatação causada pelo 1-nitro-2-feniletano em aorta de rato : provável estimulação da guanilato ciclase - Brito, Teresinha Silva de (2012)
It was early shown that intravenous treatment with 1-nitro-2-phenylethane (NPE) induced hypotension resulting mainly from its direct vasodilatory action on vascular smooth muscle. Here, it was sudied the underlying mechanism involved in the vasorelaxant effect of NPE in isolated rings of rat arteries. Isometric recordings were obtained from rings made from aorta or mesenteric artery using a digital acquisition system. Experiments in silico (docking) for simulation of molecular interactions between NPE and the enzyme guanylate cyclase were performed. In endothelium-intact aortic preparations, NPE (1-300 g/mL) relaxed the phenylephrine or K+-induced contractions with IC50 values of 35.0 [23.3- 52.6] and 73.2 [39.5-134.3] g/mL, respectively. Vasorelaxant effects of NPE were significantly (P <0.05, Mann-Whitney test) decreased by pretreatment with ODQ (10 µM), methylene blue (10 µM), TEA (5 mM), glibenclamide (10 µM) or 4-aminopyridine (1 mM) but not by vascular endothelium removal or by pretreatment with L-NAME (100 µM), indomethacin (10 µM), MDL-12.330A (3 µM), KT5823 (0.5 µM ) or KT5720 (1 µM). Pharmacological potency of NPE was significantly greater (p <0.01, Mann-Whitney test) in preparations of mesenteric artery compared to that of aorta, as in K+- and norepinephrine-induced contraction with IC50 values of 5.3 [2.6-10.5] and 6.5 [2.8-14.9] g/mL, respectively. In calcium-free medium, in presence of K+ 60 mM or phenylephrine 1 μM, the CaCl2-induced contractions were significantly reduced and almost abolished by NPE at 100 μg/mL, respectively. In calcium-free medium, containing EGTA, the contractile response of phenylephrine was significantly reduced by NPE (100 g/mL), an effect prevented by treatment with ODQ (10 µM), whereas NPE was deprived of any significant effect on caffeine-induced contractions. Similar results were obtained with sodium nitroprusside. NPE also inhibited the contractions induced by the capacitive calcium entry or by phorbol ester. In addition, docking results revealed clusters of interactions of NPE with the guanylate cyclase molecule. The present study suggests that vasorelaxant activity of NPE on rat aorta is due to its stimulatory properties on guanylate cyclase, which activates the guanylate cyclase/cGMP/K+ channels pathway.